Role of Workbooks and Teacher's Books in Lower-secondary Chemistry Education in Czechia - Karel Vojíř; Martin Rusek (Karolinum Press, 2021)
Textbooks as a prominent product of educational content's didactical transformation are usually published as a series. Textbooks are often accompanied by workbooks and teacher's books. These publications are designed to support teacher's work and can have a significant impact on the teaching practice. To deepen the understanding of chemical education at lower-secondary schools, the goal was to map chemistry teachers' use of workbooks and teacher's books. An electronic questionnaire containing close-ended questions as well as scales was used for this purpose. Information about workbooks and teacher's books' use, frequency of use, perceived importance and purpose were gathered. Whereas 63% of the 387 respondents reported using workbooks they consider important for the quality of education, teacher's books are only used by 24% of teachers, with only 4% reporting their frequent use. The results indicate that workbooks are mostly used during chemistry lessons or for student homework, however a significant share of teachers mentioned using them for lesson preparation. The absence of a teacher's book, coupled with the teachers' reluctance to use them even when available, also pointed to their approach to teaching preparation based on the search for educational content and specific activities rather than methodological support in a broader sense.